Controversies, consensuses, and guidelines on macular hole surgery by the Asia–Pacific Vitreo-retina Society (APVRS) and the Asia–Pacific Academy of Professors in Ophthalmology (AAPPO) - Nishant V. Radke; Paisan Ruamviboonsuk; David H. Steel; Tian Tian; Alex P. Hunyor; Andrew S. H. Tsai; Andrew Chang; Chung-May Yang; Chi-Chun Lai; Fangtian Dong; Jennifer I. Lim; Jay Chhablani; et al. (Eye and Vision)
Abstract Macular hole surgery, primarily pars plana vitrectomy with internal limiting membrane peeling (ILM) and gas tamponade, has become the standard of care for full-thickness macular hole (FTMH). Despite the 85% to 95% anatomical closure rate, several aspects of the procedure are well accepted whereas some may remain controversial among vitreoretinal surgeons. An international panel of experts (IPE) comprising 27 experts from 10 countries/territories was established to evaluate a total of 38 consensus statements on ILM peeling extent, vital dye selection, face-down positioning requirements, tamponade options, timing of surgery and re-surgery, management of difficult and refractory cases, and adjuvant therapies. The objective is to synthesize evidence-based real-world practice recommendations from leading global experts to guide the management of FTMH. Of the 38 statements, the IPE reached consensus (75% voted as “Strong Agreement” or “Agreement”) on 29 (76.3%). The IPE emphasized the importance of individualized patient factors—such as hole size, chronicity, lens status, and preoperative visual acuity—in surgical planning and tempering patient’s postoperative expectations. There was strong agreement on the need of adequate peeling of the ILM, adjunctive measures including the inverted ILM flap, and face-down positioning for large and refractory FTMH. Controversial statements, such as the use of air tamponade or observation of small FTMH, not reaching consensus are identified. We hope the consensus statements agreed and disagreed by the IPE would help serve as good reference and guidelines in managing FTMH.